Study on El Nino- Southern oscillation (ENSO) Event in Malaysia - Mohamad Mahathir Mohd Osman (Terengganu: Universiti Putra Malaysia Terengganu, 2014)
Twelve principal meteorological stations o f Malaysia were chosen for this ENSO (El Nino Southern Oscillation) study. Weather data obtained are between 1964-1993.